The Effect of Environmental, Social and Governance (ESG) on Firm Value in Companies Listed on the Indonesia Stock Exchange - Nur'aeni, Nur'aeni; Sari, Widya (Indonesian Journal of Economics and Management, 2023)
The implementation of Environmental, Social, and Governance (ESG) in Indonesia is still not optimal because many companies are not willing to disclose this information to the public. ESG implementation is still in a progressive stage and cannot be applied to all companies. An obstacle to the implementation of ESG in Indonesia is the low understanding of companies about the benefits of ESG. Yet management consulting firms and investors widely use ESG scores as a key index to understand a company's overall CSR performance. The impact of ESG implementation can even increase the value of the company. This study aims to explore the influence of ESG components in the form of Environmental, Social, and Governance on firm value. The research method uses a quantitative method with an associative approach. This study used 126 companies listed on the Indonesia Stock Exchange from 2019-2021 and data analysis using panel data regression. This study shows that simultaneously all ESG components have a significant effect on firm value (Tobin's Q). Partially, environmental variables have a positive and insignificant effect. Social variables have a significant negative effect on firm value (Tobin's Q). Governance variables have a negative and insignificant effect on firm value (Tobin's Q).